Sea Change: Artworks from the Perspective of a Transracial Adoptee - Badrin, Omar (2015)
The intention of this thesis is to answer two questions: a) how does the experience of transracial adoption influence the formation of one’s personal and cultural identity? And (b) how can craft traditions, media and techniques be used to create objects that act as visual metaphors for working-through problems of identity? The technique of crochet I employed allowed me to investigate, construct and represent cultural identity from the point of view of a transracial adoptee who was navigating a position in Newfoundland culture. The assimilating of the local medium is, for me, a way of finding inclusion; however, it is an inclusion that is uncomfortable and never fully established. These works acknowledge both Newfoundland culture, and the idea of “Otherness”. Through this exploration of materials and the appropriation of local methods, I presented a visual form to the difficult position of transracial adoptees, where a “visual voice” was absent.